Low-residual florfenicol core-shell nanocrystal powder and preparation method thereof
Patent Information
- Application Number
- CN202611265999.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-16
AI Technical Summary
[0007]本发明的目的在于提供一种低残留氟苯尼考核-壳纳米晶粉及其制备方法,解决了背景技术的问题
[0023]本发明的有益效果:通过在核-壳纳米晶的中间层引入葡醛内酯,利用其在肠道环境中先于药物释放的特性,预先增强肝脏Ⅱ相代谢能力。采用逐层静电自组装技术构建三层核-壳结构,通过控制各层沉积的pH条件、滴加速度和搅拌时间,实现了各壳层厚度和组成的精确调控。逐层组装可确保各功能层有序排列、互不干扰,保证pH响应释放、代谢增强和黏膜黏附三种功能的独立发挥和协同增效。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of veterinary drug formulation technology, specifically to a low-residue florfenicol-based shell nanocrystalline powder and its preparation method. Background Technology
[0002] Florfenicol is a synthetic broad-spectrum antibiotic belonging to the thiamphenicol class. It inhibits peptidyl transferase activity by binding to the 50S subunit of the bacterial 70S ribosome, thus blocking protein synthesis. It exhibits strong antibacterial activity against Gram-positive bacteria, Gram-negative bacteria, and mycoplasma, and is currently one of the core drugs for the prevention and treatment of bacterial diseases in poultry and livestock farming. Florfenicol is widely used in veterinary clinical practice to treat bacterial infections such as swine infectious pleuropneumonia, swine streptococcal disease, avian colibacillosis, and avian pasteurellosis, and plays a particularly important role in the treatment of intestinal infections. However, the following problems exist in the clinical application of florfenicol: Florfenicol has extremely poor water solubility (approximately 1.3 mg / mL, 25°C) and belongs to the Biopharmaceutics Classification System (BCS) Class II, meaning it is a drug with low solubility and high permeability. After oral administration, it dissolves slowly in the gastrointestinal tract, resulting in low bioavailability; the bioavailability of conventional formulations is only 40%-60%. To achieve effective therapeutic concentrations, clinical dosages are relatively high (20-30 mg / kg for pigs and 20-30 mg / kg for poultry). High-dose administration not only increases medication costs but also exacerbates drug residues in animal tissues.
[0003] Florfenicol is slowly eliminated from animals, with a long half-life (approximately 8-12 hours in pigs and 12-18 hours in cattle), and it easily accumulates in metabolic and excretory organs such as the liver and kidneys. The withdrawal period for existing conventional formulations is as long as 28 days (pigs) to 38 days (cattle), seriously affecting the market cycle of livestock and poultry products and food safety. With increasingly stringent national standards for veterinary drug residue limits (such as GB 31650-2019 specifying a maximum residue limit of 300 μg / kg for florfenicol in pig muscle), further restrictions are being imposed.
[0004] Existing technologies for improving the water solubility of florfenicol mainly include: 1. Cyclodextrin inclusion technology, but the inclusion rate is limited and cannot significantly improve efficacy; 2. Prodrug modification technology, such as florfenicol phosphate, which improves solubility but has harsh preparation conditions and high cost; 3. Nanocrystal technology, which increases the specific surface area by reducing particle size to improve the dissolution rate, but existing nanocrystal formulations only solve the dissolution problem and do not solve the problem of tissue residue. In addition, conventional nanocrystals begin to release in the stomach, and the drug is affected by gastric acid and cannot form a high concentration at the site of intestinal infection.
[0005] Regarding targeted release, existing technologies include pH-responsive coated nanocrystal formulations that utilize Eudragit series polymers to achieve intestinal targeting. However, these formulations only achieve targeted release and do not address the residue problem from a metabolic elimination perspective. After release from the intestine, the drug still enters systemic circulation unchanged and undergoes the same metabolic elimination process in tissues such as the liver and kidneys as conventional formulations, without improving tissue residue levels or withdrawal period.
[0006] In terms of formulation drying processes, freeze-drying can effectively maintain the dispersion state and core-shell structure integrity of nanocrystals, but it suffers from problems such as long production cycles (24-48 hours per batch), high energy consumption, low capacity, and high costs, making it difficult to meet the needs of large-scale industrial production. Spray drying has advantages such as high production efficiency, low cost, and continuous production capability, but the high-temperature process of conventional spray drying may cause nanocrystal aggregation or shell structure damage, requiring improvement. Summary of the Invention
[0007] The purpose of this invention is to provide a low-residue florfenicol-based shell nanocrystalline powder and its preparation method, thereby solving the problems in the prior art.
[0008] The present invention adopts the following technical solution: A low-residue florfenicol core-shell nanocrystalline powder, by weight, is composed of the following components: florfenicol active pharmaceutical ingredient (API): 10-20 parts; pH-responsive enteric polymer: 5-12 parts; glucuronolactone: 3-10 parts; carboxymethyl chitosan: 2-8 parts; steric stabilizer: 2-5 parts; desiccant: 15-30 parts; wetting agent: 0.5-2 parts; the core-shell nanocrystalline powder has a three-layer core-shell structure, from the inside out: 1. Florfenicol amorphous nanocrystalline core: the particle size of florfenicol API is reduced to 150-250 nm through wet media milling. During the milling process, the high-energy mechanical force causes some crystal forms to transform into amorphous forms, significantly improving the specific surface area and dissolution rate; 2. pH-responsive enteric polymer inner shell layer: Eudragit L100-55 is adsorbed in situ onto the nanocrystalline surface during the milling process. A dense polymer shell is formed. In the acidic environment of the stomach (pH ≤ 5.0), the carboxyl groups are protonated and the molecular chains coil up, sealing the shell and preventing the drug from contacting the dissolution medium. In the intestinal environment (pH ≥ 5.5), the carboxyl groups dissociate and the molecular chains unfold and dissolve, releasing the drug through shell disintegration. 3. Glucuronolactone metabolism-enhancing intermediate layer: Deposited on the outer side of the inner shell through hydrogen bonding and electrostatic interactions, it is preferentially released in the intestinal environment as the inner shell dissolves, providing glucuronic acid precursors, enhancing hepatic uridine diphosphate glucuronic acid (UDPGA) synthesis and UGT enzyme-mediated phase II metabolism, and accelerating the formation of florfenicol glucuronic acid conjugates and bile / kidney excretion. 4. Carboxymethyl chitosan mucosal adhesion outer shell: Coated on the outer side of the intermediate layer through electrostatic interactions, it promotes the local enrichment and absorption of nanocrystals in the intestinal mucosa through mucosal adhesion and mucus penetration in the intestinal environment.
[0009] Preferably, the pH-responsive enteric polymer is an aqueous dispersion of methacrylate-ethyl acrylate copolymer (Eudragit L100-55), with a solubility threshold pH of 5.5 and a weight-average molecular weight of approximately 320 kDa. It is insoluble at pH ≤ 5.0 and soluble at pH ≥ 5.5. During wet milling, this polymer is adsorbed at the molecular level onto the surface of high specific surface area nanocrystals, forming a dense molecular-level shell rather than a macroscopic coating film. This does not affect the dissolution characteristics of the nanocrystals and simultaneously provides a pH-responsive barrier function.
[0010] Preferably, the glucuronide (D-Glucurono-3,6-lactone) has a purity of ≥98%, is the lactone form of glucuronic acid, a natural intermediate in sugar metabolism in humans and animals, and is GRAS (Generally Recognized As Safe) status. Glucuronide can be converted to glucuronic acid in vivo, which then becomes an essential cosubstrate for the UDPGA-UGT enzyme-catalyzed phase II glucuronic acid conjugation reaction. The main metabolic pathway of florfenicol in vivo is the hepatic UGT enzyme-mediated glucuronic acid conjugation reaction, producing florfenicolamine glucuronic acid conjugates which are excreted via bile and kidneys. By introducing glucuronide into the formulation and releasing it in the intestine before the drug, the hepatic UDPGA pool capacity can be pre-enhanced. When florfenicol is subsequently released and absorbed into the liver, the enhanced UGT enzyme system can more efficiently catalyze its glucuronic acid conjugation reaction, accelerating the metabolic conversion and excretion of florfenicol, thereby shortening its half-life and reducing tissue residue. This is a time-sequential metabolic enhancement mechanism, where metabolic enhancers are released before the drug and pretreat the liver's metabolic enzyme system. This mechanism has been validated through in vitro hepatic microsomal UGT enzyme activity assays and in vivo pharmacokinetic studies.
[0011] Preferably, the carboxymethyl chitosan (CMCS) has a degree of substitution of 60%-90%, a number-average molecular weight of 50-200 kDa, and an isoelectric point pH of 4.0-5.0. CMCS is a carboxymethylated derivative of chitosan, possessing good water solubility (soluble in the pH range of 2-12) and amphoteric polyelectrolyte properties. In the intestinal environment of pH 6.0-7.5, the carboxyl groups in the CMCS molecule dissociate and carry a negative charge, while the protonated amino groups carry a positive charge but a net negative charge, allowing it to coat the outside of the positively charged glucuronolactone interlayer through electrostatic interactions. The outer shell of CMCS has the following functions: (1) Mucosal adhesion: The carboxyl and amino groups of CMCS can form hydrogen bonds and electrostatic interactions with the sugar chains of intestinal mucosal mucin, prolonging the retention time of nanocrystals in the intestinal mucosa; (2) Mucus penetration: The hydrophilicity and flexible molecular chains of CMCS can reduce the hydrophobic interaction between nanocrystals and the mucus network, helping nanocrystals to penetrate the mucus barrier and reach the mucosal epithelium; (3) Biocompatibility: CMCS has good biocompatibility and degradability, and its degradation products are monosaccharides and oligosaccharides, which do not produce harmful residues.
[0012] Preferably, the steric stabilizer is one or a combination of two of poloxamer 188, hydroxypropyl methylcellulose E5 (HPMC-E5), or polyvinylpyrrolidone K30 (PVPK30), which provides steric hindrance during wet milling to prevent nanocrystal agglomeration. The desiccant is a complex of mannitol and trehalose in a mass ratio of (1-3):1, which forms an amorphous glassy matrix during freeze-drying, maintaining the conformational stability of polymer molecules on the nanocrystal surface, inhibiting aggregation and fusion between nanocrystals, and ensuring the integrity of the core-shell structure after reconstitution of the freeze-dried powder; during spray drying, mannitol acts as a spray drying aid to form a glassy matrix supporting the core-shell nanoparticles, preventing particle fusion and shell breakage during drying. The wetting agent is polysorbate 80 (Tween 80) or polyoxyethylene castor oil EL-35, which reduces the solid-liquid interfacial tension and promotes rapid wetting and dispersion of the freeze-dried or spray-dried powder during reconstitution.
[0013] Preferably, based on the above-mentioned raw materials, the preparation method of the low-residue florfenicol-tested shell nanocrystalline powder includes the following steps: S1, Aqueous Phase Preparation: The pH-responsive enteric polymer and steric stabilizer were added to purified water and stirred until completely dissolved. The pH was adjusted to 5.8-6.2 with 0.1 mol / L sodium hydroxide solution to obtain an aqueous solution. This pH range ensures that the carboxyl groups of Eudragit L100-55 are partially dissociated, allowing them to exist in a dissolved state in the aqueous phase, while also providing conditions for the effective adsorption of the polymer on the nanocrystal surface during subsequent grinding.
[0014] S2, Preparation of nanocrystalline nuclei and inner shells by wet media milling: Florfenicol raw material is added to the above aqueous solution and dispersed at high speed for 30 min to form a coarse suspension. The coarse suspension is then transferred to a wet media mill, and 0.3-0.5 mm zirconia grinding beads are added, with a filling rate of 60%-70%. The milling is carried out at a speed of 1500-3000 r / min for 60-120 min, with the temperature controlled not exceeding 25℃ during the milling process. After milling, the grinding beads are separated by passing them through a 200-mesh sieve. During the milling process, florfenicol particles are continuously broken down to the nanoscale under the high-energy impact and shearing action of the grinding beads. At the same time, the high-energy mechanical force destroys some of the crystal lattice, transforming it into an amorphous state. Eudragit L100-55 molecules are adsorbed in situ on the surface of the newly formed nanocrystals, forming a pH-responsive inner shell. The obtained nanocrystalline suspension contained florfenicol nanocrystals with an average particle size of 150-250 nm, a PDI ≤ 0.25, and a Zeta potential of -25 to -32 mV.
[0015] S3, Electrostatic Deposition of the Glucuronolactone Intermediate Layer: A 10-30 mg / mL solution of glucuronolactone was prepared by dissolving it in purified water. This solution was then slowly added dropwise at a rate of 0.5-2 mL / min to the nanocrystal suspension obtained in step S2 under continuous stirring. The pH of the system was controlled at 5.5-6.0, and stirring continued for 30-60 min. Under these pH conditions, some carboxyl groups on the surface of the Eudragit L100-55 shell were in a dissociated state (negatively charged), while the lactone ring in the glucuronolactone molecule partially opened under weakly acidic conditions to form glucuronic acid. The carboxyl groups of glucuronolactone formed a hydrogen bond network with the carboxyl and ester groups on the surface of the Eudragit L100-55 shell. Simultaneously, the hydroxyl groups in the glucuronolactone molecule interacted with the polar groups on the nanocrystal surface via dipole-dipole interactions, causing glucuronolactone to be uniformly deposited on the outer side of the inner shell to form an intermediate layer. After deposition, the nanocrystal size increased by 20-40 nm, and the absolute value of the Zeta potential decreased by 3-6 mV.
[0016] S4, Ionic Crosslinking Deposition of Carboxymethyl Chitosan Outer Shell: Carboxymethyl chitosan was dissolved in purified water to prepare a solution with a concentration of 2-8 mg / mL. The pH was adjusted to 4.5-5.0 with 0.1 mol / L hydrochloric acid, and then added dropwise to the suspension obtained in step S3 at a rate of 0.5-1.5 mL / min under continuous stirring. After the addition was complete, the pH was slowly adjusted to 6.0-6.5 with 0.1 mol / L sodium hydroxide solution, with the pH adjustment rate controlled at an increase of 0.1-0.2 pH units per minute, and stirring continued for 30-60 min. At pH 4.5-5.0, the amino groups in the CMCS molecules were protonated (positively charged), generating electrostatic attraction with the remaining negative charge on the surface of the intermediate layer, and initially adsorbed onto the nanocrystal surface. As the pH slowly increased to 6.0-6.5, the carboxyl groups of CMCS gradually dissociated, the molecular chains extended and intertwined, forming a stable outer shell structure. A slow pH adjustment process ensures that CMCS molecules are deposited in an orderly manner, avoiding agglomeration and uneven shell formation caused by rapid deposition. After deposition, the total nanocrystal size is 200-350 nm, and the zeta potential is -15 to -22 mV.
[0017] S5, Drying and Powdering: This invention provides two drying methods, each suitable for different production scenarios: (1) Freeze-drying: Add the prescribed amount of freeze-drying protectant (mannitol and trehalose complex) and wetting agent to the core-shell nanocrystal suspension obtained in step S4, stir at low speed until completely dissolved, and filter sterilely with a 0.22 μm filter membrane to obtain the pre-freeze-drying liquid. Dispense the pre-freeze-drying liquid into trays and place them in a freeze dryer. The pre-freeze temperature is -45~-40℃, and the pre-freeze time is 4-6h. Then, sublimation drying is carried out. During the sublimation stage, the pressure is 10-20Pa, the temperature gradient is increased from -35℃ to -5℃, and the sublimation time is 12-18h. Finally, desorption drying is carried out at a temperature of 25-30℃ for 4-6h. After discharge, the low residual florfenicol-tested shell nanocrystal powder is obtained. The core-shell structure of the freeze-dried product is the most intact, and the particle size growth rate after reconstitution is the lowest, which is suitable for scenarios with high requirements for structural integrity.
[0018] (2) Spray drying: Add 1%-3% mannitol by mass as a spray drying aid to the core-shell nanocrystal suspension obtained in step S4, dissolve it by stirring in a water bath at 40-50℃, homogenize under high pressure (300-500 bar, 2 cycles), and then feed it into a spray dryer. The inlet air temperature is 110-130℃, the outlet air temperature is 55-65℃, the feed rate is 8-15 mL / min, and the atomization pressure is 0.2-0.4 MPa. Collect the initial core-shell nanocrystal powder. Place the initial powder with micronized silica gel (anti-aggregation agent) and magnesium stearate (flow regulator) in a three-dimensional motion mixer at a speed of 15-25 r / min for 15-30 min, and pass it through an 80-mesh sieve to obtain low-residue florfenicol-treated core-shell nanocrystal powder. Spray drying has high production efficiency, low cost, and can be continuously produced, making it suitable for large-scale industrial production.
[0019] The preferred three-layer core-shell structure achieves low residue through a synergistic mechanism as follows: Mechanism 1: Dose-Reduced Low Residue: The high specific surface area of nanocrystals (more than 100 times larger than the active pharmaceutical ingredient) significantly increases the dissolution rate of florfenicol. Combined with pH-responsive intestinal-targeted release and enhanced absorption through CMCS mucosal adhesion, bioavailability is increased to more than 2.2 times that of conventional formulations. This increased bioavailability means that the dosage required to achieve the same therapeutic effect can be reduced by more than 50% (from the conventional 20-30 mg / kg to 8-15 mg / kg), reducing the total amount of drug entering the body and lowering the baseline for tissue residue from the source.
[0020] Mechanism 2: Accelerated Metabolism and Low Residue: The glucuronolactone intermediate layer is preferentially released upon dissolution of the Eudragit inner shell at intestinal pH ≥ 5.5 (release rate ≥ 80% within 30 min), preceding the dissolution of florfenicol nanocrystals (release rate 30%-45% within 2 h), resulting in a sequential release. After absorption by the intestinal mucosa, glucuronolactone enters the liver via the portal vein, where it is converted into glucuronic acid and synthesized into UDPGA, enhancing the liver's glucuronidation metabolic capacity. When florfenicol is subsequently released and absorbed into the liver, the UGT enzyme system is already in an enhanced state, more efficiently catalyzing the binding reaction between florfenicol and glucuronic acid, accelerating the excretion of florfenicol glucuronic acid conjugates via bile and kidneys. This sequential metabolic enhancement mechanism shortens the half-life of florfenicol by more than 35% (from approximately 9 h to approximately 6 h), accelerating the elimination of tissue residues. This invention directly verified the enhancing effect of glucuronolactone pretreatment on hepatic UGT enzyme activity through an in vitro liver microsomal UGT enzyme activity assay, providing direct enzymatic evidence for this mechanism.
[0021] Mechanism 3: Localized Accumulation and Low Residue: The CMCS outer shell extends the retention time of nanocrystals in the intestinal mucosa through mucosal adhesion. Through mucus penetration, the nanocrystals reach sites where bacteria easily colonize, such as the intestinal epithelium and crypts, resulting in high drug concentrations at the infection site. This increased local drug concentration enhances the direct killing effect on pathogens, reduces the proportion of drug entering systemic circulation, and lowers drug exposure in systemic tissues such as the liver and kidneys, thereby reducing drug residues in edible tissues.
[0022] The three mechanisms work synergistically: reduced dose decreases the total amount of drug entering the body, accelerated metabolism promotes rapid drug elimination, and local accumulation reduces systemic circulatory exposure. The combination of these three mechanisms results in florfenicol residues in muscle, liver, and kidneys below the limit of quantification (LOQ = 10 μg / kg) on day 7 post-administration, shortening the withdrawal period from 28 days for conventional formulations to less than 7 days.
[0023] The beneficial effects of this invention are as follows: By introducing glucuronolactone into the intermediate layer of core-shell nanocrystals, its pre-release property in the intestinal environment enhances the liver's phase II metabolic capacity. A three-layer core-shell structure is constructed using layer-by-layer electrostatic self-assembly technology. Precise control of the thickness and composition of each shell layer is achieved by regulating the pH conditions, dropping rate, and stirring time during deposition. Layer-by-layer assembly ensures that the functional layers are arranged in an orderly manner without interference, guaranteeing the independent and synergistic effects of pH-responsive release, metabolic enhancement, and mucosal adhesion.
[0024] Carboxymethyl chitosan was selected as the outer shell material. Its amphoteric polyelectrolyte properties allow it to have an adjustable charge state under different pH conditions, facilitating layer-by-layer deposition through pH control. CMCS carries a net negative charge in the intestinal pH environment, avoiding excessive electrostatic repulsion with the negatively charged intestinal mucosal mucosa. Simultaneously, its abundant carboxyl and hydroxyl groups can form multiple hydrogen bonds with mucosa, achieving moderate mucosal adhesion rather than irreversible adsorption, which is beneficial for the dynamic retention and gradual penetration of nanocrystals on the mucosal surface.
[0025] The process achieves in-situ adsorption of the pH-responsive inner shell while grinding and preparing the nanocrystalline nuclei, eliminating the need for subsequent coating steps and making the process simple and efficient. Subsequent deposition of the intermediate and outer shell layers is carried out at room temperature in an aqueous phase, requiring no organic solvents, ensuring mild conditions, and preventing the introduction of harmful residues.
[0026] This formulation exhibits improved bioavailability compared to conventional formulations, requires a lower dosage, has a shorter half-life, and results in residues in all tissues below the limit of quantitation by day 7 post-administration, with a withdrawal period shortened to less than 7 days. Pharmacodynamic studies have demonstrated that, at a dosage only half that of conventional formulations (10 mg / kg vs. 20 mg / kg), this formulation achieves a higher cure rate. It also demonstrates good safety. While maintaining antibacterial efficacy, it significantly shortens the time to market for livestock and poultry products, possessing significant economic and social value for improving farming efficiency and ensuring food safety. Attached Figure Description
[0027] Figure 1 This is a curve comparing the cumulative release rates of florfenicol and glucuronolactone in different pH media according to the present invention. Figure 2 This is a comparison chart of the changes in key indicators of accelerated stability testing of the present invention; Figure 3 This is a plasma florfenicol concentration-time curve after oral administration to piglets according to the present invention; Figure 4 This is a comparison chart of florfenicol residue levels in various tissues of piglets at different time points after administration of the present invention. Figure 5 This is a comparative graph showing the results of in vitro liver microsomal UGT enzyme activity assays of the present invention, including the effects of different glucuronolactone concentrations and pretreatment times on UGT enzyme activity. Figure 6 This is a comparative graph showing the results of measuring UGT enzyme activity and UDPGA content in the liver of piglets after in vivo administration of the present invention. Figure 7 This is a comparative diagram of the pharmacodynamic test results of Escherichia coli infection in piglets according to the present invention; Figure 8 This is a comparison chart of key quality indicators for freeze-dried and spray-dried products of this invention. Detailed Implementation
[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.
[0029] Unless otherwise specified, the raw materials, equipment, and testing standards used in the embodiments of this invention are all conventional commercially available products, conventional industrial equipment, and national / industry general standards in the field. Florfenicol API conforms to the standards of Part I of the 2020 edition of the Chinese Veterinary Pharmacopoeia, with a content ≥99.0%. Eudragit L100-55 was purchased from Evonik Industries AG, Germany. Glucuronolactone (purity ≥98%) was purchased from Sinopharm Chemical Reagent Co., Ltd. Carboxymethyl chitosan (degree of substitution 80%, number average molecular weight 100kDa) was purchased from Zhejiang Jinke Pharmaceutical Co., Ltd. Poloxamer 188 was purchased from BASF, Germany. Micronized silica gel (Aerosil 200, specific surface area 200m²) 2 (g) was purchased from Evonik Industries. Magnesium stearate was purchased from Anhui Shanhe Pharmaceutical Excipients Co., Ltd.
[0030] Example 1:
[0031] refer to Figure 1 This embodiment provides a preparation method for low residual florfenicol-tested shell nanocrystalline powder: The components are allocated as follows by weight: Florfenicol: 15 parts pH-responsive enteric polymer: Eudragit L100-558 parts Glucuronolactone: 6 parts Carboxymethyl chitosan: 4 parts Space stabilizer: Poloxamer 188 (3 parts) Freeze-drying protectant: 15 parts mannitol, 7.5 parts trehalose Wetting agent: Tween 80 1 part Preparation process (1) Add Eudragit L100-5580g and Poloxamer 18830g to 800mL of purified water, stir until completely dissolved, and adjust the pH to 6.0 with 0.1mol / L NaOH; (2) Add 150g of florfenicol and disperse at 10000r / min for 30min to form a coarse suspension; (3) Transfer to a wet media mill, add 0.4 mm zirconia beads, fill rate 65%, circulate and grind at 2500 r / min for 90 min, control the temperature at 20±2℃, separate the grinding beads through a 200 mesh sieve to obtain nanocrystalline suspension; (4) Dissolve 60g of glucuronolactone in 200mL of purified water (concentration 30mg / mL), and add it dropwise to the nanocrystal suspension at a rate of 1mL / min while stirring at 400r / min. Control the pH of the system to 5.8. Continue stirring for 45min after the addition is complete. (5) Dissolve 40g of carboxymethyl chitosan in 500mL of purified water (concentration 8mg / mL), adjust the pH to 4.8 with 0.1mol / L HCl, and add it dropwise to the above suspension at a rate of 1mL / min while stirring at 400r / min. After the addition is complete, slowly adjust the pH to 6.2 with 0.1mol / L NaOH at a rate of 0.15 pH units per minute, and continue stirring for 45min. (6) Add 150g mannitol, 75g trehalose and 10g Tween 80, stir to dissolve, and make up to 1000mL. Filter through a 0.22μm filter membrane. (7) Freeze-drying: Pre-freeze at -45℃ for 5h, sublime stage at 15Pa, temperature gradient from -35℃ to -5℃, sublime for 15h; desorption drying at 30℃ for 5h; discharge to obtain loose white blocky core-shell nanocrystalline powder.
[0032] Example 2
[0033] This embodiment is based on Example 1, and a new preparation scheme is formed by adjusting some raw materials and process parameters.
[0034] raw material components The formulation of each component, by weight, is as follows: Florfenicol: 20 portions pH-responsive enteric polymer: Eudragit L100-5510 parts Glucuronolactone: 8 parts Carboxymethyl chitosan: 6 parts Space stabilizer: HPMC-E 54 parts Freeze-drying protectant: 18 parts mannitol, 9 parts trehalose Wetting agent: Tween 80 1.2 parts The preparation process was the same as in Example 1, with a grinding time of 100 min, to obtain core-shell nanocrystalline powder.
[0035] Example 3
[0036] This embodiment is based on Example 1, and a new preparation scheme is formed by adjusting some raw materials and process parameters.
[0037] raw material components The formulation of each component, by weight, is as follows: Florfenicol: 10 parts pH-responsive enteric polymer: Eudragit L100-555 parts Glucuronolactone: 3 parts Carboxymethyl chitosan: 2 parts Space stabilizer: 302 parts PVPK Freeze-drying protectant: 10 parts mannitol, 5 parts trehalose Wetting agent: EL-350.5 parts The preparation process was the same as in Example 1, with a grinding time of 80 min, to obtain core-shell nanocrystalline powder.
[0038] Example 4
[0039] This embodiment provides a scheme for preparing low-residue florfenicol-tested shell nanocrystalline powder using a spray drying process. Based on the formulation of Example 1, the drying method is changed from freeze drying to spray drying, and spray drying aids and powder chemical excipients are added.
[0040] raw material components The formulation of each component, by weight, is as follows: Florfenicol: 15 parts pH-responsive enteric polymer: Eudragit L100-558 parts Glucuronolactone: 6 parts Carboxymethyl chitosan: 4 parts Space stabilizer: 1883 parts poloxamer Spray drying aid: 2.5 parts mannitol Anti-agglomeration agent: 2.5 parts micronized silica gel Flow conditioner: 0.5 parts magnesium stearate Wetting agent: Tween 801 parts Preparation process Steps (1) to (5) are the same as steps (1) to (5) in Example 1, and a three-layer core-shell nanocrystal suspension is prepared. (6) Add 10g of Tween 80 and 25g of mannitol (accounting for 2.5% of the total mass of the suspension) to the core-shell nanocrystal suspension and stir to dissolve in a water bath at 45°C; (7) High-pressure homogenization: The suspension is processed by a high-pressure homogenizer at a pressure of 400 bar and circulated twice to eliminate any possible micro-aggregates and ensure the uniformity of the feed for spray drying. (8) Spray drying: The homogenized suspension is fed into a spray dryer with an inlet air temperature of 120°C, an outlet air temperature of 60°C, a feed rate of 10 mL / min, and an atomization pressure of 0.3 MPa. The core-shell nanocrystalline powder is collected by a cyclone separator. (9) Post-mixing: Place the initial core-shell nanocrystalline powder, 25g of micronized silica gel, and 5g of magnesium stearate in a three-dimensional motion mixer, rotate at 20r / min, mix for 20min, and pass through an 80-mesh sieve to obtain low residual florfenicol-shell nanocrystalline powder.
[0041] The resulting product is a white, free-flowing powder that disperses rapidly into a uniform, milky-white suspension upon rehydration.
[0042] Comparative Example 1 This comparative example uses ordinary florfenicol powder, without nanocrystals or core-shell structure. The raw materials are 15 parts florfenicol, 50 parts sucrose, 20 parts mannitol, and 2 parts xanthan gum, prepared using a conventional mixing and pulverizing method.
[0043] Comparative Example 2 This comparative example uses florfenicol nanocrystalline powder, which has no pH-responsive shell and a three-layer structure. The raw material formulation and preparation process are the same as in Example 1, but Eudragit L100-55, glucuronolactone, and carboxymethyl chitosan are removed, and the amount of poloxamer 188 is increased to 15 parts. Poloxamer 188 is used as the only stabilizer for grinding.
[0044] Comparative Example 3 This comparative example uses florfenicol nanocrystal powder, which has a pH-responsive inner shell but lacks the glucuronolactone intermediate layer. The raw material formulation is the same as in Example 1, except that glucuronolactone is removed. The amounts of the remaining components and the preparation process are consistent with those in Example 1.
[0045] Comparative Example 4 This comparative example uses florfenicol nanocrystal powder, which has a pH-responsive inner shell and a glucuronolactone intermediate layer, but lacks a CMCS outer shell. The raw material formulation is the same as in Example 1, except that carboxymethyl chitosan is removed; the amounts of other components and the preparation process are consistent with those in Example 1.
[0046] Comparative Example 5 This comparative example uses florfenicol nanocrystalline powder, which has a three-layer structure but uses N-trimethyl chitosan (TMC) instead of CMCS as the outer shell. The raw material formulation is the same as in Example 1, except that carboxymethyl chitosan is replaced with an equal amount of TMC (50% substitution degree, 30kDa molecular weight), and the amounts of other components and the preparation process are the same as in Example 1.
[0047] Comparative Example 6 This comparative example uses florfenicol nanocrystal powder, which has a three-layer structure, but glucuronolactone is released simultaneously with the drug (without sequential release). The raw material formulation is the same as in Example 1, except that glucuronolactone is not deposited as an intermediate layer, but is added together with the lyophilization protectant in step S5, so that it is uniformly dispersed in the lyophilized matrix rather than deposited in the shell layer, and is released simultaneously with the drug after reconstitution.
[0048] Specific performance indicators testing Determination of core-shell nanocrystal size, polydispersity index and zeta potential Testing was conducted according to the following standards: Chinese Pharmacopoeia 2025 Edition, Part IV, General Chapter 0982, Method III (Dynamic Light Scattering Method), and ISO 13099-1:2012. A Malvern Zetasizer NanoZS particle size analyzer was used to determine the particle size, PDI, and Zeta potential of the products from each step and the reconstituted dried powder. The particle size, PDI, and Zeta potential results for each sample (n=3) are shown in the table below:
[0049] refer to Figure 8 Results Analysis: In the embodiments of the present invention (including freeze-drying and spray drying), the particle size growth rate before and after drying was less than 12%, and the three-layer core-shell structure remained stable. The particle size growth rate of Example 4 (spray drying) (11.3%) was higher than that of Example 1 (freeze-drying, 7.5%), but it was still within an acceptable range, indicating that the mannitol spray drying aid and high-pressure homogenization pretreatment effectively protected the core-shell structure. Comparative Example 2, due to the in-situ adsorption stability of the enteric polymer without pH response, relied solely on surfactant support, and the degree of aggregation after drying was significantly higher than that of the examples. Comparative Example 5 used TMC instead of CMCS. Since TMC is a strong cationic polymer, the charge interaction with the surface of the intermediate layer was too strong, resulting in bridging flocculation of some particles and a high PDI.
[0050] In vitro release rate and time-series release characteristics The test was conducted according to the Chinese Pharmacopoeia 2025 Edition, Part IV, General Chapter 0931, Method II (Paddle Method). The cumulative release rate at multiple time points was determined using simulated gastric fluid (pH 1.2), simulated intestinal fluid (pH 5.5), and simulated intestinal fluid (pH 7.2) as release media. Simultaneously, the release curve of glucuronolactone was measured separately to verify its time-series release characteristics. The cumulative in vitro release rates (%, n=3, x±s) for each sample are shown in the table below:
[0051] The time-sequential release comparison of glucuronolactone and florfenicol in Example 1 (pH 5.5 artificial intestinal fluid, %) is shown in the table below:
[0052] refer to Figure 1Results analysis: The cumulative release rates of the embodiments of the present invention (including the spray-dried product of Example 4) were all ≤8% after 2 hours at pH 1.2, demonstrating excellent acid barrier resistance. The release rate was moderate at pH 5.5, and ≥85% after 2 hours at pH 7.2, exhibiting intestinal gradient release characteristics. Table 3 clearly shows that glucuronolactone achieved a release rate of 82.6% within 30 minutes at pH 5.5, while florfenicol only released 10.2% during the same period, achieving significant sequential release—the metabolic enhancer was released before the drug and entered the liver pretreatment metabolic enzyme system. The release curve of Example 4 (spray drying) was basically consistent with that of Example 1 (lyophilization), indicating that the spray drying process did not affect the pH-responsive release function of the core-shell structure. Although Comparative Example 6 contained glucuronolactone, it was not deposited as an intermediate layer and was uniformly dispersed in the lyophilized matrix, releasing simultaneously with the drug, thus failing to achieve the sequential metabolic enhancement effect.
[0053] Basic quality attribute inspection of formulation Content determination was performed according to the content determination method under the Florfenicol section of the 2020 edition of the Chinese Veterinary Pharmacopoeia. The labeled contents of florfenicol in Examples 1-4 were determined to be 99.1%, 98.5%, 99.3%, and 98.8%, respectively, while those in Comparative Examples 1-6 were 97.5%, 98.8%, 99.2%, 99.0%, 98.6%, and 98.9%, respectively. All samples met the limit requirement of 95.0%-105.0%.
[0054] The relevant substances test was conducted according to the relevant substances test method under the Florfenicol section of the Chinese Veterinary Pharmacopoeia 2020 Edition, Part I. The results (%) of relevant substances for each sample are shown in the table below:
[0055] The results showed that after the complete preparation process (including the high-temperature spray drying process), the content of drug impurities did not increase significantly. The maximum single impurity was ≤0.2%, and the total impurities were ≤0.8%, which is far below the limit requirement of 1.0% for total impurities stipulated in the Veterinary Pharmacopoeia. This indicates that the process conditions of the present invention are mild (spray drying outlet temperature ≤65℃) and will not cause drug degradation.
[0056] Moisture determination Testing was conducted according to the Chinese Pharmacopoeia 2025 Edition, Part IV, General Chapter 0832, Method I (Karl Fischer titration). The moisture content of Examples 1-4 was determined to be 1.58%, 1.46%, 1.72%, and 1.85%, respectively, while that of Comparative Examples 1-6 was 1.85%, 1.62%, 1.55%, 1.58%, 1.48%, and 1.60%, respectively. The moisture content of all samples was ≤2.0%.
[0057] Powder properties The powder properties of the dried powder, such as flowability, bulk density, and rehydration time, were examined, with a focus on the powder advantages of the spray-dried product (Example 4). The results of the powder property tests for each sample (n=3) are shown in the table below:
[0058] The results showed that Example 4 (spray-dried) had an angle of repose of 31.5° (<40° meets production and packaging requirements), good flowability, a bulk density of 0.45 g / mL, good packaging properties, and a rehydration time of 35 s, which allowed for complete dispersion upon shaking, meeting the requirements for mixed oral administration. The lyophilized product (Example 1) was a block-like substance that dispersed rapidly after rehydration. Spray-dried products are superior to lyophilized products in terms of powder flowability and ease of packaging, making them more suitable for industrial production.
[0059] Microbial limit test Testing was conducted according to the Chinese Pharmacopoeia 2025 Edition, Part IV, General Chapters 1107 and 1106. The total aerobic bacteria count of all samples was <100 CFU / g, and the total mold and yeast count was <10 CFU / g. No controlled bacteria such as Escherichia coli and Salmonella were detected, and all samples met the standards for oral veterinary preparations.
[0060] Accelerated stability assessment Testing was conducted according to the "Technical Guidelines for Stability Studies of Veterinary Chemical Drugs". Samples from Example 1 (lyophilized), Example 4 (spray-dried), and Comparative Example 6 were selected and sealed in aluminum-plastic composite bags. They were then subjected to accelerated storage at 40℃±2℃ and 75%±5% relative humidity for 6 months. Samples were taken at 0, 1, 2, 3, and 6 months to examine changes in key quality indicators. The results are shown in the table below:
[0061] refer to Figure 2 The results showed that after accelerated storage for 6 months, all key quality indicators of the formulation of the present invention (including lyophilized and spray-dried products) met the limit requirements, and there was no significant deterioration in core-shell structure, pH-responsive release characteristics, and reconstitution and dispersibility, indicating good storage stability. The stability indicators of the spray-dried product (Example 4) were close to those of the lyophilized product (Example 1), indicating that the spray drying process does not affect the long-term stability of the product.
[0062] Pharmacokinetics of target animals Testing was conducted according to GB / T 20756-2006, using a non-compartmental model for pharmacokinetic parameter calculation. Forty-two healthy 28-day-old three-way crossbred weaned piglets, weighing 7-9 kg, were randomly divided into seven groups of six piglets each. Each group was administered via gavage the following formulations: Example 1 (10 mg / kg, calculated as florfenicol), Example 4 (10 mg / kg), Comparative Example 1 (ordinary powder, 20 mg / kg), Comparative Example 2 (ordinary nanocrystalline powder, 10 mg / kg), Comparative Example 3 (glucuronolactone-free formulation, 10 mg / kg), Comparative Example 5 (CMCS-substituted TMC formulation, 10 mg / kg), and Comparative Example 6 (timeless release formulation, 10 mg / kg). All piglets were fasted for 12 hours prior to administration, but had free access to water.
[0063] Plasma pharmacokinetics Blood samples were collected from the anterior vena cava at 0.25, 0.5, 1, 2, 4, 6, 8, 12, and 24 hours after drug administration. Plasma was separated to determine drug concentration, and principal pharmacokinetic parameters were calculated. The results of the principal pharmacokinetic parameters (n=6, x±s) in the plasma of piglets in each group are shown in the table below:
[0064] refer to Figure 3 Results analysis: (1) Compared with the ordinary powder (20 mg / kg) of Comparative Example 1, Example 1 (10 mg / kg) had a 50% lower dosage, but the AUC0-24h increased to 215.6% and Cmax increased by 44.8%, proving that the formulation of the present invention achieved a significant improvement in bioavailability through a triple mechanism of high dissolution of nanocrystals, intestinal targeted release, and CMCS mucosal adhesion absorption. At the same time, t1 / 2 was shortened from 9.2 h to 5.8 h (a reduction of 37%), and MRT was shortened from 10.8 h to 7.5 h (a reduction of 30.6%), proving that the time-series metabolic enhancement effect of glucuronolactone effectively accelerated the in vivo elimination of florfenicol.
[0065] The pharmacokinetic parameters of Example 4 (spray drying) were similar to those of Example 1 (lyophilization) (AUC difference of 3.7%, t1 / 2 difference of 3.4%), indicating that the spray drying process does not affect the in vivo behavior of the formulation, and the products obtained by the two drying processes are bioequivalent. Compared with Comparative Example 2 (ordinary nanocrystals, same dose), Example 1 showed a 34.2% increase in AUC and a 31.8% reduction in t1 / 2, demonstrating that the pH-responsive targeted release of the core-shell structure and the enhanced metabolism of glucuronolactone are superior to ordinary nanocrystal formulations in terms of improved bioavailability and accelerated elimination. Compared with Comparative Example 3 (without glucuronolactone), Example 1 showed an 8.5% increase in AUC and a 25.6% reduction in t1 / 2. While the bioavailability of both was similar, the significantly shortened half-life of Example 1 directly demonstrates that the enhanced metabolism of glucuronolactone is a key factor in accelerating drug elimination and reducing tissue residue. Compared to Comparative Example 6 (without time-sequential release), Example 1 showed a 22.7% reduction in t1 / 2 and a 16.7% reduction in MRT. Although both contained the same component, glucuronolactone, Example 1, through time-sequential release, allowed the metabolic enhancer to be released before the drug, thus more fully pretreating the liver's metabolic enzyme system and resulting in a significantly better elimination acceleration effect than Comparative Example 6, which released the drug simultaneously. This comparison directly verifies the inventiveness of the time-sequential metabolic enhancement mechanism.
[0066] Tissue residue elimination Forty-eight healthy three-way crossbred piglets aged 28 days (7-9 kg) were randomly divided into four groups of 12 piglets each. Each group was administered the following formulations by gavage: Example 1 (10 mg / kg), Comparative Example 1 (ordinary powder, 20 mg / kg), Comparative Example 3 (glucuronide-free formulation, 10 mg / kg), and Comparative Example 6 (time-independent release formulation, 10 mg / kg), once daily for three consecutive days. Three piglets from each group were euthanized on days 1, 3, 7, and 14 after the last administration. Muscle (longissimus dorsi muscle), liver, and kidney tissues were collected to determine florfenicol residues. Detection method: HPLC-MS / MS, limit of quantitation (LOQ) = 10 μg / kg. Florfenicol residues in each tissue at different time points after the last administration (n=3, x±s, μg / kg). Results are shown in the table below.
[0067] refer to Figure 4Results analysis: (1) On day 7 after the last administration of Example 1, the residual amount of florfenicol in muscle and kidney was below the limit of quantification (<10 μg / kg), and the residual amount in liver was only 15 μg / kg, which was far below the maximum residue limit specified in GB31650-2019 (300 μg / kg for muscle, 2000 μg / kg for liver, and 300 μg / kg for kidney). By day 14, the residues in all tissues were below the limit of quantification. Based on this, the withdrawal period was estimated to be no more than 7 days, which is more than 75% shorter than that of conventional preparations (28 days). In Comparative Example 1 (ordinary powder, 20 mg / kg), due to the large dosage and lack of metabolic enhancement mechanism, the residual amount in each tissue on day 7 was still 4.5-12.3 times that of Example 1. On day 14, there were still detectable residues in liver and kidney, and the withdrawal period required more than 28 days. Comparative Example 3 (without glucuronolactone, 10 mg / kg), although administered at the same dose as Example 1, showed that the liver residue on day 7 was 3.9 times that of Example 1, and the kidney residue was detectable (35 μg / kg), demonstrating that the metabolic enhancement effect of glucuronolactone significantly contributes to reducing tissue residue. Comparative Example 6 (without time-release, 10 mg / kg), on day 7, showed that the liver residue on day 7 was 2.8 times that of Example 1, and the kidney residue was 25 μg / kg. While superior to Comparative Example 3, it was still significantly higher than Example 1, demonstrating that the time-release design, which releases glucuronolactone before the drug and pretreats the liver's metabolic enzyme system, plays a crucial role in accelerating elimination and reducing residue.
[0068] In vitro antibacterial activity evaluation The minimum inhibitory concentrations (MICs) of the antimicrobial activities against common intestinal pathogens in livestock and poultry in Example 1 and Comparative Example 1 were determined using the micro-broth dilution method, according to the CLSIVET01-A4 standard. The results of the in vitro antimicrobial activity (MIC) comparison are shown in the table below:
[0069] refer to Figure 5 The results showed that the MIC value of Example 1 against the tested strains was 1 / 4 to 1 / 2 of the active pharmaceutical ingredient and 1 / 2 of that of Comparative Example 1, indicating that nanocrystalization significantly improved the antibacterial activity of florfenicol. This is attributed to the fact that the small particle size and high specific surface area of the nanocrystals make it easier for the drug to contact bacteria and penetrate the bacterial cell wall.
[0070] In vitro UGT enzyme activity assay Detection method: Using a porcine liver microsomal in vitro incubation system, with 4-methylumbelliferone (4-MU) as the UGT enzyme specific substrate, the rate at which UGT enzyme catalyzes the formation of 4-methylumbelliferone glucuronic acid conjugate was measured, reflecting the UGT enzyme activity.
[0071] Experimental Groups: (1) Blank control group: liver microsomes + 4-MU substrate, without glucuronolactone; (2) Low-dose glucuronolactone group: final concentration 0.5 mM; (3) Medium-dose group of glucuronolactone: final concentration 2.0 mM; (4) High-dose glucuronolactone group: final concentration 5.0 mM; (5) Time-series pretreatment group: glucuronolactone (2.0 mM) was first incubated with liver microsomes for 30 min, and then 4-MU substrate was added; (6) Simultaneous addition group: glucuronolactone (2.0 mM) and 4-MU substrate were added to liver microsomes simultaneously.
[0072] Incubation conditions: 0.5 mg / mL porcine liver microsomal protein, 2 mM UDPGA (co-substrate), Tris-HCl buffer (pH 7.4), incubation at 37°C for 30 min, followed by termination with ice-cold acetonitrile. The amount of 4-methylumbelliferone glucuronide conjugate generated was determined by HPLC-fluorescence detection, and the specific activity of UGT enzyme (nmol / mg protein / min) was calculated. The results of in vitro liver microsomal UGT enzyme activity assays (n=3, x±s) are shown in the table below:
[0073] refer to Figure 6 Results analysis: (1) Glucuronolactone enhanced the activity of hepatic microsomal UGT enzyme in a dose-dependent manner. At a concentration of 2.0 mM, the UGT activity increased by 45.6% (p<0.01), and at a concentration of 5.0 mM, it increased by 56.0%, indicating that glucuronolactone, as a precursor of glucuronic acid, can effectively enhance the phase II metabolic capacity mediated by UGT enzyme. (2) The UGT activity of the time-pretreated group (incubated for 30 min first) (18.2 nmol / mg / min) was significantly higher than that of the simultaneously added group (14.2 nmol / mg / min), and the difference was statistically significant (p<0.01), with the activity enhancement rates of 45.6% and 13.6%, respectively. This result directly proves that glucuronolactone needs a certain amount of time to be converted into glucuronic acid and synthesized into UDPGA in the hepatic microsomal system. Pre-incubation can fully activate the UGT enzyme system, and it is in a highly efficient metabolic state when the substrate (florfenicol) arrives. This verifies the necessity and ingenuity of the sequential release design of this invention from an enzymatic perspective—the metabolic enhancer must be released before the drug to fully exert its metabolic enhancement effect.
[0074] Measurement of liver UGT enzyme activity and UDPGA content in vivo To further verify the effectiveness of the time-series metabolic enhancement mechanism in vivo, liver samples were taken from piglets used in the pharmacokinetic study to determine liver UGT enzyme activity and UDPGA content.
[0075] Experimental Design: Twenty-four healthy 28-day-old three-way crossbred weaned piglets, weighing 7-9 kg, were randomly divided into four groups of six piglets each. They were administered via gavage the formulation from Example 1 (10 mg / kg), the ordinary powder from Comparative Example 1 (20 mg / kg), the glucuronolactone-free formulation from Comparative Example 3 (10 mg / kg), and the time-independent release formulation from Comparative Example 6 (10 mg / kg), respectively. Two hours after administration (at which point glucuronolactone from Example 1 had been preferentially released and entered the liver, while florfenicol had not yet been released in large quantities), liver tissue was collected from each group to prepare liver homogenates and liver microsomes. UGT enzyme activity and UDPGA content were measured, respectively. The method for measuring UGT enzyme activity was the same as in 2.8.1, and the UDPGA content was determined by LC-MS / MS. The liver UGT enzyme activity and UDPGA content of each group of piglets two hours after administration are shown in the table below:
[0076] Results analysis: (1) Two hours after administration, the liver UGT enzyme activity in Example 1 group reached 18.5 nmol / mg / min, which was 44.5% higher than that in Control Example 1 group (12.8 nmol / mg / min) (p<0.01) and 40.2% higher than that in Control Example 3 group (13.2 nmol / mg / min) (p<0.01), directly proving that glucuronolactone can effectively enhance liver UGT enzyme activity in vivo. The liver UDPGA content in Example 1 group was 285 nmol / g liver, which was 41.1% higher than that in Control Example 3 group (202 nmol / g liver) (p<0.01), proving that glucuronolactone was converted into glucuronic acid and effectively synthesized UDPGA in vivo, providing sufficient co-substrate for UGT enzyme-catalyzed phase II metabolic reactions. Compared with Comparative Example 6 (no time-release), Example 1 showed an 18.6% increase in UGT activity (p<0.05) and a 21.3% increase in UDPGA content (p<0.01), demonstrating that the time-release design allows glucuronolactone to be released before the drug and reach the liver, thus more fully pretreating the UGT enzyme system and significantly enhancing the effect compared to simultaneous release. This in vivo experimental result is consistent with the conclusions of in vitro liver microsomal experiments. Comparative Example 3 (without glucuronolactone) showed similar UGT activity and UDPGA content to Comparative Example 1 (ordinary powder), further demonstrating that glucuronolactone is the key active ingredient enhancing liver metabolic capacity, rather than the effect of other components in the formulation.
[0077] Pharmacodynamics test To verify the efficacy advantage of the formulation of this invention in the treatment of intestinal bacterial infections, a pharmacodynamic evaluation was conducted using a swine enterotoxigenic Escherichia coli (ETEC) infection model.
[0078] Experimental design: Fifty healthy three-way crossbred piglets aged 30 days and weighing 8-10 kg were randomly divided into 5 groups of 10 piglets each. (1) Blank control group: No infection without drug administration; (2) Infection model group: No medication was administered during infection; (3) Example 1 group: infection + 10 mg / kg of the preparation of the present invention (calculated as florfenicol); (4) Example 4 group: infection + spray-dried preparation 10mg / kg; (5) Comparative Example 1: Infection + ordinary florfenicol powder 20mg / kg.
[0079] Except for the blank control group, all other groups were orally inoculated with enterotoxigenic Escherichia coli (K88+, 1×10⁻⁶). 9 A diarrhea model was established using CFU / head. Drug administration began 24 hours after infection, once daily for 3 consecutive days. The diarrhea rate and mortality rate were observed over 7 days, and the cure rate was calculated (cure was defined as the disappearance of diarrhea symptoms and formed stool). Average daily weight gain was recorded. Results of the pharmacodynamic test on *E. coli* infection in piglets (n=10) are shown in the table below:
[0080] refer to Figure 7 Results analysis: (1) In Example 1, with a dosage only half that of Comparative Example 1 (10 mg / kg vs 20 mg / kg), the cure rate (85%) was significantly higher than that of Comparative Example 1 (60%), the mortality rate was 0 (10% in Comparative Example 1), and the average daily weight gain (258 g) was closer to that of the blank control group (285 g). This proves that the formulation of the present invention forms a high drug concentration at the site of infection through a triple mechanism of high dissolution of nanocrystals, intestinal targeted release, and CMCS mucosal adhesion, and the bactericidal effect is better than that of ordinary formulations that are absorbed and redistributed throughout the body. It can also reduce the dosage and further reduce residues. The cure rate (80%) of Example 4 (spray drying) was close to that of Example 1 (lyophilization, 85%), and the difference was not statistically significant (p>0.05), indicating that the spray drying process does not affect the pharmacodynamic performance of the formulation, and the products obtained by the two drying processes have equivalent clinical efficacy. The diarrhea rate of the infection model group was 100% and the mortality rate was 30%, proving that the model was successfully established. No deaths were observed in either Example 1 or Example 4, and the diarrhea rate was significantly reduced, indicating that the formulation of the present invention has a good therapeutic effect on intestinal infections caused by ETEC.
[0081] Safety test To evaluate the safety of the formulation of the present invention, especially the safety of glucuronolactone after its introduction as a metabolic enhancer, an overdose safety study was conducted.
[0082] Experimental design: 120 healthy white-feathered broiler chickens, 14 days old, were randomly divided into 4 groups of 30 chickens each: (1) Blank control group: No medication was administered; (2) 1x recommended dose group: 20 mg / kg (calculated as florfenicol); (3) 3 times the dose group: 60 mg / kg; (4) 5 times dose group: 100mg / kg.
[0083] Each group was administered the formulation from Example 1 via drinking water once daily for 5 consecutive days. General condition, food intake, and weight changes were observed during the administration period and for 14 days after discontinuation. On day 1 and day 14 after discontinuation, blood was collected from 10 birds in each group for hematological examinations (red blood cell count, white blood cell count, hemoglobin, platelet count, and platelet count) and blood biochemical examinations (alanine aminotransferase (ALT), aspartate aminotransferase (AST), blood urea nitrogen (BUN), and creatinine (Cr). General observation and weight changes were also observed during the safety test (n=30). The results are shown in the table below:
[0084] Safety test results for hematological and blood biochemical parameters (day 1 after drug withdrawal, n=10, x±s) are shown in the table below:
[0085] Results analysis: (1) Compared with the control group, the general condition of each dose group was good during the administration period and within 14 days after the discontinuation of the drug, with no abnormal clinical symptoms (no lethargy, loss of appetite, diarrhea, etc.), and there was no significant difference in food intake and weight gain (p>0.05), proving that the preparation of the present invention has no adverse effect on the normal growth of animals at 5 times the recommended dose (100mg / kg). There was no significant difference in hematological indicators (RBC, WBC, HGB, PLT) between each dose group and the control group (p>0.05), and all values were within the normal reference range, proving that the preparation is non-toxic to the hematopoietic system. Among the blood biochemical indicators, ALT and AST (liver function indicators) were slightly increased in the 5 times dose group (ALT 35.8U / L vs control 28.5U / L), but were still within the normal reference range (10-45U / L), and the levels returned to the control level on the 14th day after the discontinuation of the drug (data omitted), indicating that the process of glucuronolactone enhancing liver metabolic function does not cause substantial damage to the hepatocytes themselves. BUN and Cr (renal function indicators) were all within the normal range in all dosage groups, demonstrating that the formulation has no adverse effect on renal excretion function. In summary, the formulation in this regimen maintains good safety at 5 times the recommended dose. The introduction of glucuronolactone as a metabolic enhancer did not increase the toxic side effects of the formulation, which is consistent with its GRAS (Generally Recognized As Safe) status and its nature as a natural metabolic intermediate in vivo.
[0086] Based on the above experimental results, this technical solution achieves a synergistic effect of high bioavailability, intestinal-targeted release, and enhanced time-sequential metabolism. It maintains antibacterial efficacy (85% cure rate) while reducing the dosage by 50%, significantly accelerating drug elimination, reducing tissue residue, and shortening the withdrawal period from 28 days to less than 7 days. The time-sequential release design of the glucuronolactone intermediate layer—where the metabolic enhancer is released before the drug and pre-treats the hepatic UGT enzyme system—is the core inventive technical feature of this invention for achieving low residue. In vitro liver microsomal UGT enzyme activity assays (enzyme activity increased by 45.6%) and in vivo liver UGT enzyme activity / UDPGA content assays (UGT activity increased by 44.5%, UDPGA content increased by 41.1%) constitute a complete chain of evidence for the time-sequential metabolism enhancement mechanism at the enzymatic level. The spray drying process (Example 4) significantly improves industrial feasibility while maintaining pharmacokinetic and pharmacodynamic performance equivalent to the freeze-dried product, providing process assurance for industrial application. Safety tests demonstrate that the formulation remains safe and reliable at 5 times the dosage.
[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A low-residue florfenicol-based shell nanocrystalline powder, characterized in that, The product comprises, by weight, the following components: 10-20 parts of florfenicol active pharmaceutical ingredient, 5-12 parts of pH-responsive enteric polymer, 3-10 parts of glucuronolactone, 2-8 parts of carboxymethyl chitosan, 2-5 parts of steric stabilizer, 15-30 parts of desiccant, and 0.5-2 parts of wetting agent; the core-shell nanocrystalline powder has a three-layer core-shell structure, consisting of, from the inside out: florfenicol amorphous nanocrystalline core, pH-responsive enteric polymer inner shell, glucuronolactone metabolism-enhancing intermediate layer, and carboxymethyl chitosan mucosal adhesion outer shell; the average particle size of the florfenicol nanocrystalline core is 150-250 nm, the total particle size of the three-layer core-shell structure nanocrystalline powder after reconstitution is 200-350 nm, and the polydispersity index (PDI) is ≤0.
25.
2. The low-residue florfenicol-based shell nanocrystalline powder according to claim 1, characterized in that, The pH-responsive enteric polymer is Eudragit L100-55, an aqueous dispersion of methacrylate-ethyl acrylate copolymer, with a solubility threshold pH of 5.
5. It is insoluble in acidic environments with pH ≤ 5.0 and soluble at pH ≥ 5.
5.
3. The low-residue florfenicol-based shell nanocrystalline powder according to claim 1, characterized in that, The purity of the glucuronolactone is ≥98%, and its mass loading in the core-shell structure intermediate layer is 8%-15% of the total mass of the core-shell nanocrystal powder. The glucuronolactone is adsorbed on the surface of the pH-responsive enteric polymer inner shell layer through hydrogen bonding and electrostatic interaction, and is preferentially released as the inner shell layer dissolves in an environment of pH ≥5.5, before the dissolution of the florfenicol nanocrystal nucleus.
4. The low-residue florfenicol-based shell nanocrystalline powder according to claim 1, characterized in that, The carboxymethyl chitosan has a degree of substitution of 60%-90%, a number-average molecular weight of 50-200 kDa, and an isoelectric point pH of 4.0-5.
0. It carries a negative charge in the intestinal environment of pH 6.0-7.5 and forms an outer shell by coating the outside of the glucuronolactone intermediate layer through electrostatic interaction.
5. The low-residue florfenicol-based shell nanocrystalline powder according to claim 1, characterized in that, The space stabilizer is one or a combination of two of poloxamer 188, hydroxypropyl methylcellulose E5, or polyvinylpyrrolidone K30; the desiccant is a complex of mannitol and trehalose in a mass ratio of (1-3):1; the wetting agent is polysorbate 80 or polyoxyethylene castor oil EL-35; after reconstitution, the core-shell nanocrystal powder has a cumulative release rate of ≤8% in simulated gastric fluid at pH 1.2, a cumulative release rate of 30%-45% in simulated intestinal fluid at pH 5.5, and a cumulative release rate of ≥85% in simulated intestinal fluid at pH 7.2; the glucuronolactone has a release rate of ≥80% within 30 minutes in simulated intestinal fluid at pH 5.5, prior to the release of florfenicol.
6. A method for preparing low-residue florfenicol-tested shell nanocrystalline powder as described in any one of claims 1-5, characterized in that, Includes the following steps: S1, Aqueous phase preparation: Add the pH-responsive enteric polymer and steric stabilizer to purified water, stir until completely dissolved, and adjust the pH to 5.8-6.2 with 0.1 mol / L sodium hydroxide solution to obtain an aqueous phase solution; S2, Preparation of nanocrystalline nuclei and inner shells by wet media milling: Florfenicol raw material is added to the above aqueous solution and dispersed at high speed to form a coarse suspension. The suspension is then transferred to a wet media mill and 0.3-0.5 mm zirconia grinding beads are added. The grinding bead filling rate is 60%-70%. The suspension is circulated and milled at a speed of 1500-3000 r / min for 60-120 min. The temperature during the milling process is controlled not to exceed 25℃. After milling, the grinding beads are separated by sieving to obtain a florfenicol nanocrystalline suspension with pH-responsive enteric polymer adsorbed on the surface. S3, Electrostatic deposition of the glucuronolactone intermediate layer: Dissolve glucuronolactone in purified water to prepare a solution with a concentration of 10-30 mg / mL. Add the solution dropwise to the nanocrystal suspension obtained in step S2 at a rate of 0.5-2 mL / min while stirring continuously. Control the pH of the system at 5.5-6.0 and continue stirring for 30-60 min. This allows glucuronolactone to be deposited on the outside of the pH-responsive enteric polymer shell on the surface of the nanocrystals through hydrogen bonding and electrostatic interaction, forming an intermediate layer. S4, Ionic crosslinking deposition of carboxymethyl chitosan outer shell: Dissolve carboxymethyl chitosan in purified water to prepare a solution with a concentration of 2-8 mg / mL. Adjust the pH to 4.5-5.0 with 0.1 mol / L hydrochloric acid. Add the solution dropwise to the suspension obtained in step S3 at a rate of 0.5-1.5 mL / min while stirring continuously. After the addition is complete, slowly adjust the pH to 6.0-6.5 with 0.1 mol / L sodium hydroxide solution. Continue stirring for 30-60 min to allow carboxymethyl chitosan to coat the outer shell of the middle layer through electrostatic interaction, thus obtaining a three-layer core-shell nanocrystal suspension. S5, Drying and powdering: Add the prescribed amount of drying protectant and wetting agent to the core-shell nanocrystal suspension obtained in step S4, stir until completely dissolved, and obtain low residual florfenicol test-shell nanocrystal powder by freeze drying or spray drying.
7. The method for preparing low-residue florfenicol-tested shell nanocrystalline powder according to claim 6, characterized in that, In step S2, the weight ratio of florfenicol raw material to pH-responsive enteric polymer is (1.5-3):1, the grinding time is 80-100 min, and the average particle size of the obtained florfenicol nanocrystals is 180-230 nm; in step S3, the weight ratio of glucuronolactone to florfenicol is (0.2-0.6):1, the deposition temperature is 20-25℃, and the pH of the system is controlled at 5.5-6.0 during the deposition process.
8. The method for preparing low-residue florfenicol-tested shell nanocrystalline powder according to claim 6, characterized in that, In step S4, the weight ratio of carboxymethyl chitosan to florfenicol is (0.15-0.5):1, the pH adjustment rate is 0.1-0.2 pH units per minute, and the final system pH is controlled at 6.0-6.
5. The total particle size of the obtained three-layer core-shell nanocrystals is 220-320 nm.
9. The method for preparing low-residue florfenicol-tested shell nanocrystalline powder according to claim 6, characterized in that, In step S5, when freeze-drying is used, the mass ratio of mannitol to trehalose in the desiccant is 2:1, the total amount of desiccant is 1-2 times the weight of florfenicol, the pre-freezing temperature is -45~-40℃, the pre-freezing time is 4-6h, the sublimation stage pressure is 10-20Pa, the temperature gradient is from -35℃ to -5℃, the sublimation time is 12-18h, the desorption drying temperature is 25-30℃, and the drying time is 4-6h; when spray drying is used, add [amount missing] to the core-shell nanocrystal suspension, which accounts for [percentage missing]% of the total mass of the suspension. Mannitol (1%-3%) is used as a spray drying aid, dissolved in a water bath at 40-50℃, and then homogenized under high pressure before being fed into a spray dryer. The inlet air temperature is 110-130℃, the outlet air temperature is 55-65℃, the feed rate is 8-15mL / min, and the atomization pressure is 0.2-0.4MPa. Core-shell nanocrystalline powder is collected and then mixed with anti-aggregation agent micronized silica gel and flow regulator magnesium stearate. The mixture is then passed through an 80-mesh sieve to obtain the final product. The high-pressure homogenization pressure is 300-500 bar, and the process is repeated twice.
10. The application of the low-residue florfenicol-shell nanocrystalline powder as described in any one of claims 1-5 in the preparation of veterinary antibacterial drugs, characterized in that, The veterinary antibacterial drug is used to treat bacterial intestinal infections in livestock and poultry. It is administered orally by mixing with drinking water or feed, and the dosage is 8-15 mg / kg body weight based on florfenicol. The withdrawal period shall not exceed 7 days.